Spatial-Problem Based Learning (SPBL) development (preliminary studies for geography learning) - Waode Yunia Silviariza; Budi Handoyo (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2020)
Problem Based Learning (PBL) is one of the scientific learning models that is widely used by teachers to educate students about the subjects they teach. PBL is widely developed and applied in all fields of multidisciplinary science. Therefore, PBL in learning geography needs to be developed to fit the main characteristics of geography, namely the spatial approach. In geography learning, the Spatial Based Learning (SBL) model is often used. SBL is a model that can encourage students to think in space. Therefore, integrating PBL and SBL will create a new learning model that is more in line with the characteristics of geography learning that presents spatial phenomena or problems. The purpose of this research is to develop a PBL model for learning geography. Design research development using Borg and Gall [1] with eight steps, namely: (1) needs analysis, (2) planning, (3) developing initial product forms, (4) initial field testing, (5) major product revisions, ( 6) carrying out field testing, (7) product revisions, and (8) final product revisions. The subjects of the study were geography students, Universitas Negeri Malang, and the validator was a doctor in geography education. Data collected by in-depth interviews and questionnaires. In-depth interviews are used to collect data from expert validators, while questionnaires are used to collect data from students. Data from expert validation is used to improve the learning model developed. Data from students is used to determine the feasibility of the resulting model. Data analysis was performed descriptively and statistically. The results of the development mentioned Spatial Problem Based Learning (SPBL). It has five steps, namely: (1) spatial problem orientation, (2) formulating spatial problems, (3) collecting and organizing spatial data, (4) analyzing spatial data and discussion, and (5) communication. The results of validation by experts showed a score of more than 65%. Field test results show that the average score of the five development steps is 93.2. Based on trials that the SPBL syntax is feasible